2021
DOI: 10.3390/pharmaceutics13071097
|View full text |Cite
|
Sign up to set email alerts
|

Simplified 89Zr-Labeling Protocol of Oxine (8-Hydroxyquinoline) Enabling Prolonged Tracking of Liposome-Based Nanomedicines and Cells

Abstract: In this work, a method for the preparation of the highly lipophilic labeling synthon [89Zr]Zr(oxinate)4 was optimized for the radiolabeling of liposomes and human induced pluripotent stem cells (hiPSCs). The aim was to establish a robust and reliable labeling protocol for enabling up to one week positron emission tomography (PET) tracing of lipid-based nanomedicines and transplanted or injected cells, respectively. [89Zr]Zr(oxinate)4 was prepared from oxine (8-hydroxyquinoline) and [89Zr]Zr(OH)2(C2O4). Earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In a study using the same location of the implants and the same type of nanoparticles an accumulation of nanoparticles at the implant after 24 h could be seen [ 34 ]. Zirconium-89 ( 89 Zr) which is commonly used in clinical nuclear imaging, and due to its longer half-life of 78.4 h it allows longer tracking periods of up to several days [ 85 ]. This would allow repeated scanning of the animals at later time points without additional injections, which might reveal any later changes in particle distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study using the same location of the implants and the same type of nanoparticles an accumulation of nanoparticles at the implant after 24 h could be seen [ 34 ]. Zirconium-89 ( 89 Zr) which is commonly used in clinical nuclear imaging, and due to its longer half-life of 78.4 h it allows longer tracking periods of up to several days [ 85 ]. This would allow repeated scanning of the animals at later time points without additional injections, which might reveal any later changes in particle distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it can also be attached via a chelator molecule which might make it easy to transmit to the here presented nanoparticles [ 86 ]. Labeling nanoparticular systems with 89 Zr is already described in the literature [ 85 , 87 ]. However, as long as the blood circulation time of the nanoparticles is not increased it is questionable whether a longer study time would reveal any changes in nanoparticle distribution because a redistribution of particles caught in the RES organs is not likely to happen.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabeling method optimization of 89 Zr, PET imaging probe [129] Although extensive efforts have been devoted to pharmacokinetic studies of radioliposomes, the research outcomes have been unsatisfactory in the last few decades due to various factors, such as rapid blood clearance, early drug release, low bioavailability, and non-targeted delivery. For example, 99m Tc-labeled liposomes failed to accumulate in several types of tumors even though similar tissue distributions of radioliposomes were found in these models (particularly high in the liver and spleen, moderate accumulation in the kidney and bone marrow) [75,86].…”
Section: Liposomal Probe Name Isotope Application and Research Outcomesmentioning
confidence: 99%
“…Additionally, results showed that 89 Zr-labeled liposomes accumulated in the lymph node at a later time point since 89 Zr has a high affinity for macrophages [128,133]. However, these supporting documents were insufficient for 89 Zr-labeled liposomes to be approved for use as a diagnostic probe in future clinical settings; hence, further optimization of labeling strategies for liposome labeling with 89 Zr should be prioritized to overcome the downsides [129].…”
Section: Liposomal Probe Name Isotope Application and Research Outcomesmentioning
confidence: 99%
“…The long half-life of 89 Zr, offering a biologically more meaningful prolonged cell tracking time (even one or two weeks), deserves a special mention. Given its widespread commercial availability, [ 89 Zr]Zr(oxinate) 4 was already used for the labelling of the following various cell types: tumor cell lines, bone marrow and dendritic cells, therapeutic T cells, and stem cells (seen in Figure 3) [68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: Cell and Stem Cell Trackingmentioning
confidence: 99%